2018
DOI: 10.1111/flan.12318
|View full text |Cite
|
Sign up to set email alerts
|

Technology and the future of language teaching

Abstract: We are living in a time with unprecedented opportunities to communicate with others in authentic and compelling linguistically and culturally contextualized domains. In fact, language teachers today are faced with so many fascinating options for using technology to enhance language learning that it can be overwhelming. Even for those who are inclined to experiment with emerging technologies, it can be challenging to identify which resources, tools, or Web sites may best fit a particular lesson, activity, or go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(248 citation statements)
references
References 27 publications
2
176
0
11
Order By: Relevance
“…However, current call teacher education is still problematic, with issues that prohibit teachers from learning as much about call as they might (Başal, 2015;Hanson-Smith, 2016;Kessler, 2016Kessler, , 2018; one of the most salient issues is the lack of sufficient and appropriate courses in the curriculum (Dudeney, Hockly, & Pegrum, 2013;Hubbard, 2008;Peters, 2006). Hubbard (2008) noted over ten years ago that the most common approach to call teacher education was a single course with a selection of technological tools; Hanson-Smith (2016) notes that this trend has not changed much.…”
Section: Current State Of Call Teacher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, current call teacher education is still problematic, with issues that prohibit teachers from learning as much about call as they might (Başal, 2015;Hanson-Smith, 2016;Kessler, 2016Kessler, , 2018; one of the most salient issues is the lack of sufficient and appropriate courses in the curriculum (Dudeney, Hockly, & Pegrum, 2013;Hubbard, 2008;Peters, 2006). Hubbard (2008) noted over ten years ago that the most common approach to call teacher education was a single course with a selection of technological tools; Hanson-Smith (2016) notes that this trend has not changed much.…”
Section: Current State Of Call Teacher Educationmentioning
confidence: 99%
“…Hubbard (2008) noted over ten years ago that the most common approach to call teacher education was a single course with a selection of technological tools; Hanson-Smith (2016) notes that this trend has not changed much. This common approach typically features lecture with a focus on existing technologies (Kessler, 2018;Kessler & Hubbard, 2017), and many studies have found it to be less than effective in helping language teachers integrate technology effectively (e.g., Hegelheimer, 2006;Peters, 2006).…”
Section: Current State Of Call Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers should be trained and prepared for teaching in a digital era, effectively using various tools. Teachers will face the overwhelming opportunities and choosing the relevant ones will be a major challenge (Kessler, 2018). They should also be ready to embrace blended teaching approach, mobile learning, concept of paperless teaching.…”
Section: Future Of English Language Teachingmentioning
confidence: 99%
“…There is abundant research literature detailing the many ICT applications and their practice in the foreign language classroom (Blake, 2016; Guan, 2014;Huang, 2014;Kessler, 2018;Levy, 2009;Park, Yang & Hsieh, 2014). The younger generations of language instructors who are now very familiar with the latest gadgets in technologies do not hesitate to put to test a variety of public and private programs and software.…”
Section: The Foreign Language Reading Brain: Reading On Screen and Pementioning
confidence: 99%